ANALISIS MAJAS DALAM LIRIK LAGU DAERAH SAMBAS - Astrea Astrea; Ahadi Sulissusiawan; Deden Ramdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract.This thesis is titled "Analysis of Majas in Sambas Regional Song Lyrics." The problems in this study are the comparison, the discussion of contradictions, the interrelationships, and the repetition in the Sambas regional song lyrics. This study aims to analyze the comparison, the content of the contradictions, the interrelationships, and the repetition in the Sambas regional song lyrics. The method in this research is descriptive method. The form of research used is qualitative research. The source of the data in this study is the Sambas song lyrics which became the background song or soundtrack of the Sambas film and the song by Bulyan Mustafa. The data in this study are comparisons, contradictions, linkages, and repetitions in Sambas regional song lyrics. The data collection technique in this study is documentary study. The data collection tool in this study is the author himself as a key instrument. The data analysis technique used in this study is descriptive qualitative. Based on the results of the data description and data analysis, it can be concluded that there are 7 lyrics of the comparison comparison, 3 lyrics of the contradiction, 6 lyrics of the contradictions, and 19 lyrics of the repetition.  Keywords:Figure of Speech, Lyrics, Sambas Regional Songs